Markov model in proving the convergence of fuzzy genetic algorithm - Manh Tuan, Tran; Ba Dung, Le (Vietnam Journal of Science and Technology, 2017)
Genetic Algorithms (GA) was concerned by many authors and researchers from all over the world. There were results in different fields of our lives. But the convergence of GA is an open problems. In this paper, we propose a method using Markov model to prove the convergence of GA. At first, in section 2, we review fundamental concepts in Markov Model, then we present important role of Markov model in GA (section 3). After that, in section 4, we show the weak convergence of GA base on Markov model. In the end, in section 5, we also illustrate these using experiment results.